2006
DOI: 10.1016/j.jacc.2006.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Detection and Alerting for Acute ST-Segment Elevation Myocardial Ischemia Using an Implantable, High-Fidelity, Intracardiac Electrogram Monitoring System With Long-Range Telemetry in an Ambulatory Porcine Model

Abstract: This study demonstrates the ability of an implantable ischemia detection system to detect ST-segment elevation from coronary occlusion in a porcine model of ST-segment elevation myocardial infarction. ST-segment elevation was sufficient to trigger alerting thresholds in all 3 epicardial coronary distributions. Such a system, with real-time alerting capability, could advance the time frame of reperfusion therapy and potentially prevent, rather than interrupt, acute myocardial infarction in patients with coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…In an animal study, changes in the ST-segment recorded by implanted leads occurred earlier than those recorded from surface ECG leads, thus conferring an ability to quickly detect myocardial ischemia. 28,29 Innovative technology that uses specialized electrodes that measure pectoral muscle bioimpedance has suggested that changes in tissue impedance can provide estimates of systemic blood pressure. 30 …”
Section: Identification Of Clinical Deteriorationmentioning
confidence: 99%
“…In an animal study, changes in the ST-segment recorded by implanted leads occurred earlier than those recorded from surface ECG leads, thus conferring an ability to quickly detect myocardial ischemia. 28,29 Innovative technology that uses specialized electrodes that measure pectoral muscle bioimpedance has suggested that changes in tissue impedance can provide estimates of systemic blood pressure. 30 …”
Section: Identification Of Clinical Deteriorationmentioning
confidence: 99%
“…Intracardiac ECGs are superior at detecting ischemia compared with body‐surface ECGs and can detect ischemia earlier than surface ECGs 9, 10, 11, 12. A comparison of the intracardiac ECG vectors of an ischemic state—from the tip of the right ventricle (RV) to the ICD can, from the tip of the RV to the right atrium (RA), and from the RA to the ICD can—showed that the ST change in the intracardiac ECG from the tip of the RV to the ICD can was sensitive 11.…”
Section: Introductionmentioning
confidence: 99%
“…Early detection and prompt intervention of an acute myocardial infarction significantly improves the clinical outcome. The mean time from myocardial infarction symptom onset to arrival at a hospital for treatment is about 2.5 to 3 hours [2,3]. Surveys and focus groups of heart patients, family members, and the public report that they thought the presenting symptoms were less dramatic then expected.…”
Section: Background and Clinical Importancementioning
confidence: 99%
“…Many patients take a "wait and see" approach until they are more certain of the symptoms significance [4]. A large proportion of irreversible myocardial injury and fatal ventricular arrhythmias occur in the first several hours after closure of a coronary artery [2,3]. The longer the time between closure of the artery and the treatment lead to further myocardial necrosis and worse clinical outcomes [3].…”
Section: Background and Clinical Importancementioning
confidence: 99%
See 1 more Smart Citation